Pengaruh Penggunaan Media Pembelajaran Presentasi Berbasis Animaker Terhadap Hasil Belajar Siswa Pada Pembelajaran IPA di Kelas V Madrasah Ibtidaiyah Negeri 4 Sumbawa - Sakti, Hadi Gunawan; Saphutra, Khaaerul Inshan (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2024)
One of the learning model that can help students in the learning process is Animaker-based Presentation Learning Media. Animaker-based Presentation Learning Media. It is expected that the learning media can improve student learning outcomes. The formulation of problem in this study is whether there is an effect of using animaker-based presentation learning media on student learning outcomes. Animaker-Based Presentation Learning Media on Student Learning Outcomes On Science Learning in Class V Madrasah Ibtidaiyah Negeri 4 Sumbawa Academic Year 2024/2025. In this study using the population study method one group pretest-posttest design. The results of this study showed that there was an increase in learning outcomes in the learning process, this fact shows that the tcount value is greater than the t-table (11.173>1.725). t-table (11.173>1.725). Thus the alternative hypothesis (Ha). Which reads that there is an Effect of Using Animaker-Based Presentation Learning Media on Student Learning Outcomes. Animaker Based Presentation Learning Media on Student Learning Outcomes in Science Learning in Class V Madrasah Ibtidaiyah Negeri 4 Sumbawa Academic Year 2024/2025. This research can be concluded, there is an effect of the use of animaker-based presentation learning media on student learning outcomes. Animaker-Based Presentation on Student Learning Outcomes in Science Learning in Grade V of Madrasah Ibtidaiyah Negeri 4 Sumbawa in the academic year 2024/2025. 2024/2025 academic year. By using teaching materials based on learning media can improve student learning outcomes as seen from the pretest-posttest of students who have increased students who have increased. Keywords: Media, Learning, Animaker, Science Learning Abstrak: Salah satu model pembelajaran yang dapat membantu siswa dalam proses pembelajaran adalah Media Pembelajaran Presentasi Berbasis Animaker. Diharapkan media pembelajaran tersebut dapat meningkatkan hasil belajar siswa. Adapun rumusan masalah dalam penelitian ini adalah Apakah Ada Pengaruh Penggunaan Media Pembelajaran Presentasi Berbasis Animaker Terhadap Hasil Belajar Siswa Pada Pembelajaran IPA Di Kelas V Madrasah Ibtidaiyah Negeri 4 Sumbawa Tahun Ajaran 2024/2025. Dalam penelitian ini menggunakan metode studi populasi one group pretest-posttest design. Hasil dari penelitian ini menunjukkan bahwa adanya peningkatan hasil belajar dalam proses pembelajaran, kenyataan ini menunjukkan bahwa nilai thitung lebih besar dari pada ttabel (11,173>1,725). Demikian hipotesis alternatif (Ha) yang berbunyi ada Pengaruh Penggunaan Media Pembelajaran Presentasi Berbasis Animaker Terhadap Hasil Belajar Siswa Pada Pembelajaran IPA Di Kelas V Madrasah Ibtidaiyah Negeri 4 Sumbawa Tahun Ajaran 2024/2025. Penelitian ini dapat disimpulkan, adanya Pengaruh Pengaruh Penggunaan Media Pembelajaran Presentasi Berbasis Animaker Terhadap Hasil Belajar Siswa Pada Pembelajaran IPA Di Kelas V Madrasah Ibtidaiyah Negeri 4 Sumbawa Tahun Ajaran 2024/2025. Dengan menggunakan bahan ajar berbasis media pembelajaran dapat meningkatkan hasil belajar siswa yang dilihat dari pretest-posttest siswa yang mengalami peningkatan. Kata Kunci: Media, Pembelajaran, Animaker, Pembelajaran IPA